T-cell responses in colorectal peritoneal metastases are recapitulated in a humanized immune system mouse model - Saris, Job; Bootsma, Sanne; Verhoeff, Jan; Tuynman, Jurriaan B.; Wildenberg, Manon E.; Rijnstra, Esther Siteur-van; Lenos, Kristiaan J.; Garcia Vallejo, Juan J.; Vermeulen, Louis; Grootjans, Joep (Frontiers in Immunology, 2024)
The occurrence of peritoneal metastasis (PM) in patients with colorectal cancer (CRC) has a dismal prognosis. There is often limited response to systemic-and immunotherapy, even in microsatellite unstable (MSI) CRC. To overcome therapy resistance, it is critical to understand local immune environment in the peritoneal cavity, and to develop models to study anti-tumor immune responses. Here, we defined the peritoneal immune system (PerIS) in PM-CRC patients and evaluate the preclinical potential of a humanized immune system (HIS) mouse model for PM-CRC.We studied the human PerIS in PM-CRC patients (n=20; MSS 19/20; 95%) and in healthy controls (n=3). HIS mice (NOD-scid gamma background; n=18) were generated, followed by intraperitoneal injection of either saline (HIS control; n=3) or human MSS/MSI CRC cell lines HUTU80, MDST8 and HCT116 (HIS-PM, n=15). Immune cells in peritoneal fluid and peritoneal tumors were analyzed using cytometry by time of flight (CyTOF).The human and HIS mouse homeostatic PerIS was equally populated by NK cells and CD4 + -and CD8 + T cells, however differences were observed in macrophage and B cell abundance. In HIS mice, successful peritoneal engraftment of both MSI and MSS tumors was observed (15/15; 100%). Both in human PM-CRC and in the HIS mouse PM-CRC model, we observed that MSS PM-CRC triggered a CD4 + Treg response in the PerIS, while MSI PM-CRC drives CD8 + TEMs responses. In conclusion, T cell responses in PM-CRC in HIS mice mirror those in human PM-CRC, making this model suitable to study anti-tumor T cell responses in PM-CRC.